Physiology of B cells in mice with X-linked immunodeficiency (xid). III. Disappearance of xid B cells in double bone marrow chimeras (The Rockefeller University Press, 1984)
Evidence is presented that B cells from mice with X-linked immunodeficiency (xid) differentiate at a slower rate than normal B cells. This conclusion stems from studies in which (B6 X CBA/J)F1 mice were heavily irradiated (1,000 rads) and reconstituted with a mixture of T-depleted marrow cells taken from (a) nondefective B6 mice (H-2b) and (b) xid CBA/N or nondefective CBA/Ca mice (both H-2k). With transfer of CBA/Ca plus B6 marrow cells, the irradiated recipients become repopulated with B cells derived from both parental marrow sources; except for an early imbalance (probably reflecting Hh resistance), the degree of chimerism remained relatively stable over a period of more than 6 months. Very different results occurred with transfer of a mixture of xid CBA/N and normal B6 marrow. Within the first 2 months after marrow reconstitution, a low but significant proportion of the B cells in both spleen and lymph nodes were of CBA/N origin. Thereafter the proportion of these cells fell progressively, and by 6-9 months virtually all of the B cells were of B6 origin. This gradual decline in CBA/N-derived cells did not apply to other cell types, i.e., T cells or pluripotential stem cells. Analogous results were obtained with transfer of CBA/N vs. CBA/Ca marrow cells into sublethally irradiated (750 rads) (CBA/N X DBA/2)F1 male vs. female mice. For example, CBA/N-marrow derived B cells differentiated effectively and survived for long periods in F1 male mice (xid----xid) but not in F1 female mice (xid----normal). The finding that xid B cells eventually disappear in the presence of normal B cells strengthens the view that xid B cells are an abnormal population not represented in normal mice.